Teaching-Service-Community Integration Practices: the experience of health care mental in the family health strategy (Research, Society and Development, 2021)
Objective: to explain the experiences of second-year medical students regarding the implementation of the intervention project in mental health in a Family Health Unit (FHU) in the city of Jequié, Bahia, Brazil. Methodology: this is an experience report, showing the construction of the intervention project of the discipline Integration Teaching, Service and Community Practices and the results achieved at the FHU. Activities were monitored: home visits, lectures in the waiting room, Integrative and Complementary Practices, health fair, and matrix support; complementing the study, the Self-Reporting Questionnaire (SRQ-20) tool was used and the training of health professionals for later use of the tool in the community was used. Results: in the context of the students, the bond with the community made it possible to know the daily lives of patients, in its biopsychosocial scope, and contributed to humanized medical training. Professionals showed interest in improving the services offered, although there was resistance to operationalize activities in the unit's routine. The population that participated in the proposed activities rated them positively, despite the low adherence, limiting the scope of interventions. Conclusion: the lived experience proved to be beneficial for the consolidation of a new form of mental health care for patients at the FHU, consisting of teaching-service-community integration.